Meaningful, gamified training of reading fluency - Massler, Ute; Müller, Wolfgang; Iurgel, Ido; Haake, Susanne; Gantikow, Alexander; Hadzilacos, Thanasis (Frontiers in Computer Science, 2022)
Improving learners’ reading is of importance. The digital world is centred on the written word, and today’s labour market requires high literacy levels. Furthermore, the development of school and foreign language skills among learners, especially those of weaker learners, is crucial as the effects of globalisation allow for increased work mobility and the necessity for lifelong learning. GameLet provides effective training scenarios for reading fluency, a prerequisite for reading comprehension, in schools with gamified, self-guided, personalised, media-based individual and collaborative learning, thereby allowing educators to intensify and extend learning activities to out-of-school settings. At the core of GameLet lies the production of a podcast by the learners that encourages them to read repeatedly, hence improving their reading fluency, and to successfully record their role in a digital Recording Studio. Increasing reading fluency is targeted by means of media-supported individual and cooperative learning phases with various training methods. Furthermore, GameLet implements meaningful digital media-based Gamification mechanisms for the purpose of increasing student motivation. The software is web-based and was developed with a focus on user-centred design and an agile and design-based approach. Prototype development followed an iterative and participative process, in which students and teachers of three participating partner countries interacted with the developed materials. Artefacts were tested in both face-to-face and online settings. GameLet exemplifies the successful application of Gamification for improving and extending classical learning scenarios at school as well as the design of effective learning technologies that are meaningful, gamified, effective and usable.